Practical Implications of Nanodosimetry in Medicine - Jahangir A. Satti (SAGE Publishing, 2012)
The grandiose promises made decades ago of cost reduction, miracle cures for cancers and universal availability of nanomedicine are still a far cry. Even we do not have any viable model to exploit nanotechnology in medicine. The most important arena of the nanotechnology is the development of nanoscale drugs for routine clinical practice. The current chemo protocols are based on maximum tolerable dose philosophy. Such a dose, when translated into active nanoscale clusters, quantitatively outnumbers the cells in an average human body. These nanoscale drug issues are discussed in this paper. A theoretical framework for commonly used drug aspirin has been considered as an example. The possible quantum physical effects have also been theoretically evaluated. Further, the amount of drug molecules in a standardized aspirin dose of 100 milligram has been computed into nanoclusters. The calculations show that the processing of nanoscale drug is a monumental task which requires new types of manufacturing facilities. Also there is a need to develop new protocols which will help realize the practical implementation of nanodosimetry in day to day drug administrations. These protocols will need to examine the implications of dose-responses such as necrosis, apoptosis and hormesis in medicine for routine clinical practice.